Development of the Export Potential of Ukraine in the Context of Innovations of the International Mining and Metallurgical Companies (Economics and region, 2020)
The paper analyzes export portfolio of Ukraine involving evaluation of status of the products manufactured by mining-metallurgical companies. Structure and balance of the external trade of Ukraine with the emphasis on leading countries-partners and main export product groups are identified. Innovative product of mining and metallurgical companies, i.e. direct reduced iron favouring sustainable national development, are characterized. Technological features and economic factors of the expedient direct reduced iron production are determined. Conditions of the global direct reduced iron market are analyzed: geographical structure of production, export, and import. Ukrainian practice in the implementation of projects for direct reduced iron production on the basis of Ukrainian iron-ore raw material is studied. Demand of the Ukrainian metallurgical plants for direct reduced iron is considered. Factors favouring the product manufacturing in such system as “direct reduced iron – high-quality steel – high-technology products with high added value” are specified. Proposals concerning the intensifications of Ukrainian export potential are formulated.
Keywords: export potential; innovations; direct reduced iron; global market; mining and metallurgical enterprises